2013
DOI: 10.1007/978-3-642-40480-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel eHealth Services for Citizen Use – Current System Engineering vs. Best Practice in HCI

Abstract: Abstract.Many new public eHealth Services are now being developed. Often a conventional customer-vendor process is used, where the customer is a public authority, e.g. a county council, and the vendor a commercial actor, e.g. an IT development company. In this case study the engineering process regards a novel eHealth service aiming to provide patients with online access to their electronic health record. A complicating factor in conventional customervendor processes for public e-services is that "the future u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…17 Previous researches on the implementation of PAEHR in Sweden have investigated the patient perspective, 9,16 as well as the implementation process used. 18 Some studies have examined the initial experiences for health-care professionals. [19][20][21][22][23][24] These studies show that a large majority of the health-care professionals had concerns related to contacts with patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous researches on the implementation of PAEHR in Sweden have investigated the patient perspective, 9,16 as well as the implementation process used. 18 Some studies have examined the initial experiences for health-care professionals. [19][20][21][22][23][24] These studies show that a large majority of the health-care professionals had concerns related to contacts with patients.…”
Section: Introductionmentioning
confidence: 99%
“…Illustrating examples are found mainly in Scandinavian research studies of user participation where the possibility to take an independent position has been seen as natural elements in research since the 1970s [20,21]. Scandurra, Holgersson, Lindh and Myreteg [9] report findings from a case study on the development process of online electronic health records. They found that external user inclusion during the development process was limited to a few poorly documented focus group meetings with patient organisations with no real impact on the development process.…”
Section: Related Researchmentioning
confidence: 99%